Optimalisasi Pengawasan Harian Mantri Menggunakan Aplikasi Android Berbasis Location Based Service - Ona Maliki; Syaifuddin Syaifuddin; Hamka Witri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Information technology has greatly facilitated our various activities, such as finding food, finding locations, using online motorcycle taxis, discussing online, and sending goods. The Tilongkabila Prosperous Citizens Cooperative is one of the cooperatives that aims to provide money-lending services for the community around the Bone Bolango district. Location Based Service is a service that can be accessed through a smartphone, which can detect the user's location and provide information about places around them based on the current location. The cooperative has many employees called Mantri. Mantri's job is to do billing. The need for supervision of orderlies who are working using Location Based Services (LBS) provides various significant benefits for cooperatives. Research objectives Supervision of orderlies at the Tilongkabila Prosperous Citizens Cooperative is carried out to ensure compliance with duties, prevent abuse of working time, increase effectiveness and productivity, and ensure transparency and accountability. With effective supervision, cooperatives can immediately identify and address problems, improve the quality of service to customers, and assist in the evaluation of orderly performance. The method used in this study is the Waterfall Method, which describes the process of making a system carried out linearly and sequentially, similar to a waterfall that flows in the direction from one stage to the next. The results showed that Location Service (LBS) for orderly supervision at the Tilongkabila Prosperous Citizens Cooperative increased task compliance, reduced abuse of working time, and increased effectiveness and productivity. LBS enables more transparent and accountable real-time monitoring, making it easier to identify and resolve issues. The quality of service to customers increases because orderlies can serve more efficiently and on time, increasing customer satisfaction. Orderly performance evaluations are becoming more structured and data-driven, supporting better development and training decisions.